"Marimbondos": a review on the neotropical swarm-founding polistines. - Fernando Barbosa Noll (Universidade Estadual de Feira de Santana, 2014)
Neotropical swarm-founding polistines, the Epiponini, compose a highly social tribe of vespids which displays several complex social characteristics, such as: intricate nest building, polygyny, swarm reproduction, and the absence of morphology caste discontinuities, a trait that would not be expected for a highly eusocial group. The biology of Epiponini will be reviewed, evidencing the scarcity of information for this group and also that not all social insects might fit in traditional theories for the evolution of social behavior.